Energy-Saving and Sustainable Separation of Bioalcohols by Adsorption on Bone Char. (15th January 2021) - Becerra-Pérez, Oslery; Georgopoulos, Stavros; Lanara, Maria; Reynel-Ávila, Hilda Elizabeth; Papadaki, Maria; Bonilla-Petriciolet, Adrián; Mendoza-Castillo, Didilia Ileana
Abstract : The separation of ethanol, propanol, and butanol from aqueous solutions was studied using adsorption on bone char. Adsorption kinetics and thermodynamic parameters of this separation method were studied at different conditions of pH and temperature. Results showed that the maximum adsorption capacities of these bioalcohols were obtained at pH 6 and 20°C. An exothermic separation was identified, which can be mainly associated to hydrophobic interactions between bone char surface and bioalcohols. Binary adsorption studies were also performed using mixtures of these bioalcohols. An antagonistic adsorption was observed for all bioalcohols where the ethanol and propanol separation was significantly affected by butanol. A model based on an artificial neural network was proposed to correlate both single and binary adsorption isotherms of these bioalcohols with bone char. It was concluded that the bone char could be an interesting adsorbent for the sustainable separation and recovery of bioalcohols from fermentation broths, which are actually considered emerging liquid biofuels and relevant industrial chemicals.